Islamic legal authority in the Indonesian legal system: a historical-normative analysis from the fiqh siyasah perspective - Mohammad Lukman Chakim; Irzak Yuliardy Nugroho (LP3M Universitas Islam Zainul Hasan Genggong, 2026)
This study aims to analyze the authority of Islamic law in the Indonesian national legal system using the theoretical frameworks of authority and persuasive sources from H. Patrick Glenn, as well as the perspective of fiqh siyasah. This study uses a historical-normative method, tracing the development of Islamic law from the colonial period to post-independence, and analyzing its authority in the current legal system in Indonesia. The results of the study indicate that during the colonial period, Islamic law functioned primarily as a persuasive source, namely, religious norms implemented socio-religiously without formal binding force within the state's legal structure. However, after independence, Islamic law underwent a significant transformation through normative recognition in laws and regulations, such as Law No. 1 of 1974/19 of 2019 and Law No. 7 of 1989 concerning Religious Courts. The existence of these laws implies that Islamic legal norms become legal, binding, and have legal consequences. This transformation from persuasive norms to authoritative norms does not conflict with the principles of the rule of law or the character of Indonesia as a Pancasila state, but rather reflects the dialogical and complementary relationship between religion and the state. In the fiqh siyasah perspective, the state is seen as having the legitimacy to adopt Islamic legal values oriented towards justice and public benefit into positive law.